2010
DOI: 10.1002/jcb.22695
|View full text |Cite
|
Sign up to set email alerts
|

Gab1 mediates hepatocyte growth factor‐stimulated mitogenicity and morphogenesis in multipotent myeloid cells

Abstract: Hepatocyte growth factor (HGF)-stimulated mitogenesis, motogenesis and morphogenesis in various cell types begins with activation of the Met receptor tyrosine kinase and the recruitment of intracellular adaptors and kinase substrates. The adapter protein Gab1 is a critical effector and substrate of activated Met, mediating morphogenesis, among other activities, in epithelial cells. To define its role downstream of Met in hematopoietic cells, Gab1 was expressed in the HGF-responsive, Gab1-negative murine myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…GAB1 belongs to the Grb2‐associtated binder (Gab) family which are scaffolding adapter molecules involved in transducting key signals that control cell growth and differentiation from multiple receptors such as growth factors, cytokines and antigen receptors . It has been implicated in tumor occurrence, invasion and metastasis, particularly in gastrointestinal tumors . Recent reports have shown that GAB1 promotes tumorigenesis by acting as an “accomplice” of certain oncoproteins or by amplifying the signaling from multiple receptors .…”
Section: Discussionmentioning
confidence: 99%
“…GAB1 belongs to the Grb2‐associtated binder (Gab) family which are scaffolding adapter molecules involved in transducting key signals that control cell growth and differentiation from multiple receptors such as growth factors, cytokines and antigen receptors . It has been implicated in tumor occurrence, invasion and metastasis, particularly in gastrointestinal tumors . Recent reports have shown that GAB1 promotes tumorigenesis by acting as an “accomplice” of certain oncoproteins or by amplifying the signaling from multiple receptors .…”
Section: Discussionmentioning
confidence: 99%
“…GAB1 functions as a mediator in growth factor signaling and cytokine receptor, especially in EGF signaling, HGF signaling and Platelet-derived growth factor (PDGF) signaling which stimulates the migration of epithelial, mesenchymal and hematopoietic cells during embryogenesis and branching morphogenesis of epithelial cells. The deficiency of GAB1 results in the lack of ligands, receptors and signaling molecules and develop the organs [30-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that GAB1 orchestrates signaling from a variety of cell surface receptor kinases such as EGFR (21,30), ERBB2 (18), and c-MET (31,32). GAB1 is phosphorylated by the activated receptor kinases at multiple tyrosine sites and recruits downstream signaling proteins such as SHP2 and PI3K, which in turn lead to activation of MAPK and AKT, respectively.…”
Section: Discussionmentioning
confidence: 99%